Comparative study between Brazil, China and India on the usage of compulsory licenses for HIV patented medication - Thiebaut, Renata (Conjuntura internacional, 2014)
In a globalized world there is a growing investment in research and technological innovation together with an eminent need to implement a more specific international document on trade related to intellectual property. The Agreement on Trade-Related Aspect of Intellectual Property Rights (TRIPS) arose in this field and the Pharmaceutical Industry is an example to be studied. The Pharmaceutical Industry has an important bargaining tool for developing countries, but it has been approached differently by Brazil, India and China. The three nation’s positioning over compulsory licensing is the reflection of their internal needs to combat Human immunodeficiency virus epidemic, and other severe diseases. The linkage between domestic law, health care and social policies and programs are the driven force to determine their international attitude. As the three governments have applied different focused differently in the three fields, a mutual cooperation approach is paramount for combating HIV epidemic.